Safety and patient experience with at‐home infusion of ocrelizumab for multiple sclerosis. Issue 4 (22nd February 2023) - Barrera, Britney; Simpson, Haley; Engebretson, Eric; Sillau, Stefan; Valdez, Brooke; Parra‐González, José; Winger, Ryan C.; Epperson, Lou Anne; Banks, Ashley; Pierce, Kathryn; Spotts, Melanie; O'Gean, Katie; et al.
Abstract: Objective: This study aimed to evaluate safety (infusion‐related reactions [IRRs]) and patient satisfaction (patient‐reported outcomes [PROs]) for at‐home ocrelizumab administration for patients with multiple sclerosis (MS). Methods: This open‐label study included adult patients with an MS diagnosis who had completed a ≥ 600‐mg ocrelizumab dose, had a patient‐determined disease steps score of 0 to 6 and had completed PROs. Eligible patients received a 600‐mg ocrelizumab home‐based infusion over 2 h, followed by 24‐h and 2‐week post‐infusion follow‐up calls. IRRs and adverse events (AEs) were documented during infusions and follow‐up calls. PROs were completed before and 2 weeks post infusion. Results: Overall, 99 of 100 expected patients were included (mean [SD] age, 42.3 [7.7] years; 72.7% female; 91.9% White). The mean (SD) infusion time was 2.5 (0.6) hours, and 75.8% of patients completed their ocrelizumab infusion between 2 to 2.5 h. The IRR incidence rate was 25.3% (95% CI: 16.7%, 33.8%)—similar to other shorter ocrelizumab infusion studies—and all AEs were mild/moderate. In total, 66.7% of patients experienced AEs, including itch, fatigue, and grogginess. Patients reported significantly increased satisfaction with the at‐home infusion process and confidence in the care provided. Patients also reported a significant preference for at‐home infusion compared with prior infusion center experiences. Interpretation: IRRs and AEs occurred at acceptable rates during in‐home infusions of ocrelizumab over a shorter infusion time. Patients reported increased confidence and comfort with the home infusion process. Findings from this study provide evidence of the safety and feasibility of home‐based ocrelizumab infusion over a shorter infusion period.